2004
DOI: 10.4049/jimmunol.173.8.4838
|View full text |Cite
|
Sign up to set email alerts
|

Marrow Stromal Cells and Osteoclast Precursors Differentially Contribute to TNF-α-Induced Osteoclastogenesis In Vivo

Abstract: The marrow stromal cell is the principal source of the key osteoclastogenic cytokine receptor activator of NF-κB (RANK) ligand (RANKL). To individualize the role of marrow stromal cells in varying states of TNF-α-driven osteoclast formation in vivo, we generated chimeric mice in which wild-type (WT) marrow, immunodepleted of T cells and stromal cells, is transplanted into lethally irradiated mice deleted of both the p55 and p75 TNFR. As control, similarly treated WT marrow was transplanted into WT mice. Each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(188 citation statements)
references
References 30 publications
6
180
0
2
Order By: Relevance
“…Several previous studies have indicated that LPS induces the expression of inflammatory cytokines, such as TNF-a, IL-1, and IL-6, in vitro and in vivo. Furthermore, it has been reported that TNF-α induces M-CSF expression in stromal cells in vivo [42,44]. In our study, we found that LPS induced M-CSF expression in vivo.…”
Section: The Inhibitory Effect Of the Anti-c-fms Antibody In Pathologsupporting
confidence: 69%
“…Several previous studies have indicated that LPS induces the expression of inflammatory cytokines, such as TNF-a, IL-1, and IL-6, in vitro and in vivo. Furthermore, it has been reported that TNF-α induces M-CSF expression in stromal cells in vivo [42,44]. In our study, we found that LPS induced M-CSF expression in vivo.…”
Section: The Inhibitory Effect Of the Anti-c-fms Antibody In Pathologsupporting
confidence: 69%
“…Bone marrow stromal cells are indeed responsible for most of the effects of TNF-α and IL-1β on bone resorption through RANKL secretion [8]; and osteoblasts are responsible for bone formation. Figure 4 indicates that, while stromal cells and osteoblasts do not constitutively express ST2L mRNA, expression o this transcript is induced by TNF-α and IL-1β (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, bone resorption due to estrogen deficiency in women can be blocked by etanercept and anakinra, which are inhibitors of TNF-α or IL-1β respectively [6]. The mechanisms used by TNF-α and IL-1β to promote bone loss include activation of osteoclastogenesis, which occurs both directly [7,8] and through the induction of receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony stimulating factor (M-CSF) expression by stromal cells [8,9]. It is also generally recognized that both cytokines contribute to decrease bone mineral density by decreasing bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…4A). Although the mechanisms underlying the enhanced osteoclastogenesis in hTNFtg mice may include the induction of RANKL in mesenchymal cells (11,14,27) or the increase in the number of osteoclast precursor cells in vivo (21,28), this result suggests a novel mechanism (i.e., the enhancement of the osteoclastogenic potential in the hTNFtg BMMs). Flow-cytometric analysis indicated that freshly isolated hTNFtg BMMs expressed a higher level of PIRs than WT BMMs, supporting the notion that the osteoclastogenic potential in the hTNFtg BMMs is enhanced (Fig.…”
Section: Fcr␥-dependent Enhanced Osteoclastogenic Potential Of Bmms Frommentioning
confidence: 92%
“…Interestingly, the anti-TNF-␣ antibody has been shown to suppress bone damage in patients who had no clinical improvement in terms of pain and inflammation (19), suggesting that, under arthritic condition, TNF-␣ exerts an important direct action on bone, which is independent of its action on the immune system. Although there has been no in vivo evidence that TNF-␣ induces osteoclastogenesis in mice lacking RANKL signaling or that TNF-␣ rescues osteopetrosis in such mice (20)(21)(22), TNF-␣ clearly acts on osteoclast precursor cells and changes the responsiveness of the cells under certain conditions (13)(14)(15). However, the molecular mechanism underlying the enhanced osteoclastogenic potential of osteoclast precursor cells in the presence of TNF-␣ remains to be elucidated.…”
mentioning
confidence: 96%